Concrete Destruction : Costs and Damages of the Concrete and Cement Industry and the Future of Construction - Ackers, Tom; Kunze, Conrad; Orozco, Paulina; Schmelzer, Matthias; Urbanus, Nils (Rosa-Luxemburg-Stiftung, 2026)
Concrete, the final product of cement, is both omnipresent and invisible. It is the most-used man-made material and responsible for 8 % of global carbon emissions. It is associated with the destruction of soils, lifeless “concrete jungles” of modern cities, and climate breakdown. Even so, the industry that produces it has so far largely avoided public attention, compared to aviation or fossil fuels. It is rarely targeted by activists, and the social and ecological costs and damages of this material have eluded public debates. Concrete is so extensively used, so abundant in our surroundings, that its presence is simply taken for granted. It appears to be so useful that its ever-expanding artificial landscapes are seen as inevitable, even natural. Just as water is invisible to fish, concrete escapes our critical analysis. This is even more true of the cement industry, which, as the “infrastructure of infrastructure”, is even more hidden from everyday life. --
Keywords: sementtiteollisuus; päästöt; betoni; rakennusaineet; kestävä kehitys; sementti; ilmastonmuutokset; rakennusteollisuus